THE INCULCATION MODEL OF REGION MODERATION VALUES IN ISLAMIC SENIOR HIGH SCHOOL (MADRASAH ALIYAH) - Said Subhan Posangi; Damhuri (LP2M IAIN Sultan Amai Gorontalo, 2024)
The challenge in promoting religion moderation values is going to be very complex in this recent era, due to many violences happened in schools in the form of verbal, psychological, or physical. However, madrasah (Islamic school) as an educational institution which always struggle to minimalize the deviant behaviors as the result of the lack of tolerance, equality, diversity, and the others. Therefore, this study aimed to reveal the strategy of the inculcation of religion moderation values in private Islamic senior high schools (private madrasah aliyah) in Gorontalo. Furthermore, the qualitative research method was used to study the strategies implemented by five private Islamic senior high schools in Gorontalo in inculcating various moderation values. This study aimed to show that the model of the inculcation of religion moderation values consisted of some models namely introduction model, habituation model, exemplary model, and the inculcation of the values in the school environment. Even there was a similarity in the inculcation of those values, the school (madrasah) also had the differences supported by some backgrounds such as environment, school organization, facility, human resource, activity, and the others. Therefore, this study concluded that the strategy implemented referring to the structural model. However, the differences of the structural model reflected to the different culture or rules which indicated that the strategy of the inculcation of religion moderation values used the structural model based on the local culture of the madrasah.